Assessment Keterampilan Menulis Ilmiah Mahasiswa Melalui Implementasi Model Pembelajaran Berbasis Riset Berbantuan Media Contoh, Template dan Pedoman Penulisan Makalah - Muhammad Syazali; I Ketut Widiada; Aisa Nikmah Rahmatih; Hasnawati Hasnawati; Ilmi Solihana Hayati; Baiq Olivia Dwita Elvira (Jurnal Ilmiah Profesi Pendidikan, 2025)
The low level of students' writing skills indicates that concrete efforts are needed to overcome these problems. In this study, we assessed students' scientific writing skills through the implementation of a research-based learning model (RBL) assisted by media Examples, Templates and Guidelines for writing papers (ETG). The research was conducted at the PGSD Study Program at Mataram University. The sample consisted of 64 students from two different batches, namely second-year students and third-year students. The instrument used to measure students' scientific writing skills was a science research paper document that they wrote individually. The scores obtained were converted into quantitative scores with a range of 0 - 100, qualitative scores (E - A) and then interpreted into 5 categories (very poor - excellent). The quantitative values were further analyzed using descriptive statistics to obtain mean, standard deviation, minimum value, maximum value and percentile data. Meanwhile, the qualitative values and their interpretation were analyzed using percentages. The results of the analysis showed that the students' scientific writing skills were at a value of 77.27. This quantitative value has grade B with good interpretation. From the results of the percentage analysis, it is known that as many as 47% of students have achieved a score of 75 and above, where the grade is B to A. Based on this data, it can be concluded that the implementation of the PBR model assisted by ETG media is effective in facilitating students to develop their scientific writing skills.